The Application Of Islamic Business Ethics To Traditional Stall Traders In Maintaining Business Sustainability Amid The Rise Of Modern Retail In Sambas District - Munadi; Raden Muhammad Tarhan; Ahmad Zabidi (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2023)
The subject matter of this study discusses the application of Islamic Business Ethics to traditional stall traders who are affected by the presence of modern retail. Furthermore, from the subject matter can be drawn several formulations of the problem, namely 1) whether the impact of the rise of modern retail for the sustainability of traditional stalls in the District. Sambas 2) is a traditional stall traders in the District. Sambas understands and applies Islamic Business Ethics in its business 3) How is the sustainability of traditional warung business in Kec. What is the role of Sambas in implementing Islamic Business Ethics?. The type of research is Field Research (Field Research) with descriptive qualitative methods of analysis. Location of the study was conducted in the District of Sambas Sambas regency. The research approach used includes normative theological, sociological and phenomenological approaches. With data sources that are divided into two, namely primary data sources obtained directly from traders or buyers and secondary data sources obtained from various literature relevant to the discussion of research. Data collection methods include observation, interviews and documentation for further data collected are analyzed through data reduction, data singing and then draw conclusions. The results of this study indicate that: 1) the presence of modern retail in the middle of traditional stalls have a negative impact on the sustainability of its business, while traditional stall traders who feel the positive impact or help from the existence of modern retail is only a little, and unevenly felt by all traditional stall traders. 2) the traditional warung traders in Sambas Sub-District have applied most of the Islamic ethics to their traditional warung business, although almost all traders feel unfamiliar or unfamiliar with the term Islamic Business Ethics and its details. 3) the application of Islamic Business Ethics to traditional stall traders in the midst of the rise of modern retail in Sambas district can maintain the sustainability of their businesses. The implication of this study is the need to provide education to traditional stall traders related to Islamic business ethics, business management, utilization of technology, as well as the provision of riba-free capital. Furthermore, it invites the public to keep shopping at traditional stalls and asks the government to determine the right zone for modern retail so as not to have a negative impact on the business of traditional stalls in the vicinity.